Quantifying the contribution of environmental variables to cyclists’ exposure to PM2.5 using machine learning techniques - Rodríguez Núñez, Martín (2024)
Fil: Rodríguez Núñez, Martín. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales; Argentina.